2018
DOI: 10.1016/j.envint.2018.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Recent exposure to particle radioactivity and biomarkers of oxidative stress and inflammation: The Framingham Heart Study

Abstract: Background: Decay products of radioactive materials may attach to ambient fine particles and form radioactive aerosol. Internal ionizing radiation source from inhaled radioactive aerosol may contribute to the fine particulate matter (PM2.5)-inflammation pathway. However, few studies in humans have examined the associations. Objectives: To examine the associations between particle radioactivity and biomarkers of oxidative stress and inflammation among participants from the Framingham Offspring and Third Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…Mice exposed to low doses of gamma radiation also developed evidence of chronic pulmonary inflammation (Christofidou-Solomidou et al, 2015). As evidence of a systemic effect of PM radioactivity in persons without COPD, in members of the Framingham Heart Study, Li et al (2018) found that exposure to higher PM radioactivity was associated with higher circulating levels of IL-6 and P-selectin. Another recent study also found higher PM radioactivity was associated with an elevation in both diastolic and systolic blood pressure (Nyhan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mice exposed to low doses of gamma radiation also developed evidence of chronic pulmonary inflammation (Christofidou-Solomidou et al, 2015). As evidence of a systemic effect of PM radioactivity in persons without COPD, in members of the Framingham Heart Study, Li et al (2018) found that exposure to higher PM radioactivity was associated with higher circulating levels of IL-6 and P-selectin. Another recent study also found higher PM radioactivity was associated with an elevation in both diastolic and systolic blood pressure (Nyhan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that long-term exposure to high concentrations of PM 2.5 increases the risk of a number of cardiorespiratory illnesses, such as asthma [6], bronchitis [7], chronic obstructive pulmonary disease (COPD) [8], coronary artery disease [9] and heart failure [10]. As revealed by many toxicological studies, the adverse health effects of PM 2.5 are associated with enhanced inflammation and oxidative stress [11,12]. Considering that ambient PM 2.5 has maintained high levels for several years and air quality could not be improved in a short period, it is urgent to find effective therapeutic approaches for attenuating PM 2.5 associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the properties that make PM toxic and can lead to the development of GDM have not been elucidated. A property that has been proposed is particle radioactivity, the radioactive component of PM in the air, which also is associated with markers of inflammation and oxidative stress [ 12 ].…”
Section: Introductionmentioning
confidence: 99%